SME Responses to Climate Change in Southeast Asia” (Trends in Southeast Asia 2022 No. 2) - Michael T. Schaper (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
Climate change is not only one of the great challenges of this century for governmentsand individuals; it is also a major issue for the millions of micro-, small- and mediumsized businesses (SMEs) that exist across.